2019
DOI: 10.3390/su11185033
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Stone Bunds on Vegetation and Soil in an Area Reforested with Pinus engelmannii Carr. in the Forests of Durango, Mexico

Abstract: The forest ecosystems of Mexico experience soil degradation mainly due to water erosion, which causes low vegetation regeneration. One of the strategies to diminish soil loss is through the construction of stone bunds (SB)—hand-made structures to trap sediment and store water for longer periods. However, little is known about their effects on pine establishment. The objectives of this study were to evaluate the effect of SB on the survival and growth of individual P. engelmannii Carr. specimens with respect to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
2
1
0
Order By: Relevance
“…At GW1 or GW2, Bu seemed to have been suitable for herbaceous growth, even if the differences were sometimes not significant. Similar result was observed by Ponce-Rodríguez et al [38] who highlighted the importance of the effect of stone bunds on the growth of herbaceous vegetation. According to Klik et al [39], the areas near the stone bunds offer better conditions for the development of the vegetation due to the retention of solids and the accumulation of mulch (organic matter, litter, etc.)…”
Section: Development Of Growth Height Of Herbaceous Speciessupporting
confidence: 89%
“…At GW1 or GW2, Bu seemed to have been suitable for herbaceous growth, even if the differences were sometimes not significant. Similar result was observed by Ponce-Rodríguez et al [38] who highlighted the importance of the effect of stone bunds on the growth of herbaceous vegetation. According to Klik et al [39], the areas near the stone bunds offer better conditions for the development of the vegetation due to the retention of solids and the accumulation of mulch (organic matter, litter, etc.)…”
Section: Development Of Growth Height Of Herbaceous Speciessupporting
confidence: 89%
“…ReviTec structures seemed to have been suitable for tree growth. Similar result was observed by Ponce‐Rodríguez et al (2019) who highlighted the importance of the effect of Stone Bunds on the growth of vegetation. According to Klik et al (2017), the areas near the Stone Bunds offer better conditions for the development of the vegetation due to the retention of solids and the accumulation of mulch (organic matter, litter, etc.)…”
Section: Discussionsupporting
confidence: 89%
“…Some authors have reported that the presence of established conservation works based on contour lines cuts the hydrological connectivity of the slope, which slows surface runoff, extends the infiltration time throughout its structure, and lets moisture remain on the ground for a longer term [20,21].…”
Section: Discussionmentioning
confidence: 99%